Production and commercialization of piloncillo:case of the community of Aldzulup Poytzen, San Luis Potosí - Baca del Moral, Julio; Cuevas Reyes, Venancio; Rosales Nieto, César A.; Rivera Martínez, Gerardo (Revista Mexicana de Ciencias Agrícolas, 2018)
The objective of the present work was to characterize the production and commercialization of piloncillo in three types of producers in the community of Aldzulup Poytzen, San Luis Potosí. Through non-probabilistic sampling, 36 producers, 17 partners, 10 former members of an organization and 9 producers without organizational experience were interviewed. The study of the scalar variables was carried out by analysis of variance for comparison of means. The three types of producers have similar socioeconomic characteristics, have an age range of 52 to 61 years, an agricultural area of less than 5.3 hectares and an average of 1 to 1.43 planted with sugar cane. The area planted with cane is temporary, the most widely used variety is ZMex 55-32, they do not use fertilizers or pesticides. The 97.3% is linked to the market through the sale of piloncillo, there is no significant difference (p< 0.05) between the income obtained from the sale of industrial piloncillo and pellets. The 86.1% of the commercialization of the piloncillo is made through stockists of the same community. It is concluded that new marketing models should be sought and promoted to obtain a greater margin of profit for the piloncillo producers.
Keywords: income; intermediaries; markets; sugarcane